The Effect of Money Ethics on Ethical Attitutes with Religiosity as the Moderating Variable - Fitri Ella Fauziah; Murharsito Murharsito (Media Ekonomi dan Manajemen, 2019)
This study aims to examine the influence of money ethics on ethical attitudes and to examine the influence of religiosity in moderating the relationship between money ethics and ethical attitudes.The population used in this study were all accounting students at Nahdlatul Ulama Islamic University in Jepara. The research sample was taken by purposive sampling method, 87 students elected as the research sample. The analysis technique used in the study is a residual test. This study used primary dataÂ  by distributing questionnaires to students of the accounting department of the Islamic University of Nahdlatul Ulama 'Jepara. The results of the study showed that money ethics has no effect on ethical attitudes and religiosity cannot moderate the relationship between money ethics and ethical attitudes.The implication of this research is that ethics education is still needed in University, so that they have an understanding related to it.